PER3P1 pseudogene modulates PER3 oscillation: a new player in the molecular clock network. Issue 12 (2nd December 2022) - Najari-Hanjani, Parisa; Farazmandfar, Touraj; Golalipour, Masoud
ABSTRACT: The circadian clock allows the body to coordinate physiology with the light and dark cycles of the day. One of the critical components of the molecular clock machinery is the PER family of circadian clock genes, including PER1, PER2, and PER3 . The PER3P1 (or PER4 ) is the only molecular clock-related pseudogene that has been derived from the PER3 gene. Pseudogenes have an essential role in the regulation of gene expression. In this study, we investigated the PER3P1 fluctuations and their effects on the PER3 expression level. We hypothesized that the PER3P1 pseudogene suppresses clock-related miRNAs and positively affects clock genes levels. The results showed that PER3P1 and its parent gene had a corresponding oscillatory expression pattern. The overexpression of PER3P1 increased the mRNA level of PER3 . In contrast, the downregulation of PER3 decreased PER3P1 expression. Furthermore, PER3P1 modulates the expression level of other clock genes, including PER1, PER2, CRY1, and CRY2 . Our results suggest that the PER3P1 pseudogene may positively affect the PER3 and other clock-related gene expressions.